Maize GSK3-like kinase ZmSK2 is involved in embryonic development. (May 2022) - Wang, Yan; Xu, Jianghai; Yu, Jingjuan; Zhu, Dengyun; Zhao, Qian
Abstract: Grain size and weight are closely related to the yield of cereal crops. Abnormal development of the embryo, an important part of the grain, not only affects crop yield but also impacts next-generation survival. Here, we found that maize GSK3-like kinase ZmSK2, a homolog of BIN2 in Arabidopsis, is involved in embryonic development. ZmSK2 overexpression resulted in severe BR defective phenotypes and arrested embryonic development at the transition stage, while the zmsk2 knockout lines showed enlarged embryos. ZmSK2 interacts with Aux/IAA-transcription factor 28 (ZmIAA28), a negative regulator of auxin signaling, and the interaction region is the auxin degron "GWPPV" motif of ZmIAA28 domain II. Coexpression of ZmSK2 with ZmIAA28 increased the accumulation of ZmIAA28 in maize protoplasts, which may have been due to phosphorylation by ZmSK2. In conclusion, this study reveals the function of ZmSK2 in maize embryonic development and proposes that ZmSK2-ZmIAA28 may be another link in the signaling pathway that integrates BR and auxin. Highlights: ZmSK2 is involved in the embryonic development of maize. ZmSK2 interacts with ZmIAA28 at the auxin degron "GWPPV" motif of domain II. ZmSK2 phosphorylates and may stabilize ZmIAA28 to integrate BR and auxin.